DUKUNGAN SOSIAL DAN SPIRITUAL DENGAN KUALITAS HIDUP LANSIA DIABETES MELITUS DI KELURAHAN LIMO - Amelia Diah Wardani; Diah Ratnawati; Tatiana Siregar (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Diabetes mellitus is often called a chronic disease caused by pancreatic organs that cannot produce insulin normally. The perception of social support is an individual's view of the support that comes from other people who can provide comfort both physically and psychologically. Spiritual is important for the elderly to realize health and restore or to maintain their health. Quality of life is the extent to which physical, environmental, social and psychological ties are perceived to meet individual needs. The purpose of this study was to identify the relationship between perception of social and spiritual support with quality of life in elderly with diabetes mellitus in Kelurahan Limo. This research is a descriptive analytic study with a cross sectional design. The sample consisted of 61 respondents with probability sampling data collection techniques with stratified random sampling. The data obtained were analyzed by Chi square test with significance (p <0.05). Chi square test results show that there is a significant relationship between the perception of social and spiritual support with the quality of life in elderly DM in Limo Village with their respective results (p = 0.048 and p = 0.026). It is recommended for families with diabetes mellitus elderly to be able to use this information to improve the quality of life of elderly people with diabetes mellitus.